(untitled) (European Journal of Education and Psychology, 2011)
Between November 2007 and June 2009 an international project aimed to establish, run and evaluate anti-bullying peer support systems in one secondary school in each of England, Italy and Spain. School anti-bullying peer support systems typically involve some pupils being selected and trained to help pupils. Using a 2 group pre-test post-test control group design, we have helped train school peer supporters and establish peer support systems in the intervention schools. For the evaluation of the programme, 248 involved and non-involved students and 35 involved and non involved teachers were surveyed using an open-end questionnaire. Here we report the outcomes of this evaluation study based on data already gathered in Spain. The results point at the positive evaluation of the programme by teachers and students, who both alike stress the positive impacts on the victims and peer supporters and see it as a resource for improving schools’ daily life.